Study of Generalized q-Close-to-Convex Functions Related to Parabolic Domain. (4th February 2023) - Noor, Khalida Inayat; Lupas, Alina Alb; Shah, Shujaat Ali; Sibih, Alanod M.; Abdel-Khalek, S.
Abstract : The concepts of bounded boundary rotation and parabolic domain are used to define certain new classes of analytic functions such as V 1, q m, g, R 1, q m, g, T 1, q m, g, and Q 1, q γ m, g, a . The difference of coefficients, necessary conditions, distortion bounds, radius problem, and several other interesting properties of these newly defined classes are also studied.